The Tale of a Disappearing Lagoon: A Habitat Mapping and Ecological Assessment of Fosu Lagoon, Ghana. (4th November 2019) - Essel, Bernard; Gyesi, Justice Kwame; Addo, Richmond Kofi; Galley, Wisdom; MacCarthy, Gideon
Abstract : Coastal regions of Ghana are primarily engaged in sea and lagoon fishing. Like many lagoons in Ghana, Fosu lagoon is a major source of livelihood for its surrounding communities. However, the lagoon and its associated marsh vegetation is under serious threat from human-induced interference. Due to this, the lagoon is considered as one of the most polluted lagoons in Ghana. Also, studies reveal that a major conservation challenge is the lack of inventory for the lagoon's associated vegetation. Hence, the research was to map and assess the lagoon's habitat and identify threats to the lagoon. In achieving the research objectives, remote sensing and GIS technique were used to effectively map the lagoon and the catchment area. The result indicated that the Fosu lagoon is characterized by a massive decline in lagoon size and the vegetation cover. Thus, the standing water has declined by 50.2 acres from 1970 to 2017 to physical development and weeds. Also, it was evident in the result that the lagoon's vegetation is now fragmented into six various vegetation types and the weeds in the lagoon make approximately one-third of the lagoon's vegetation cover. Also, adding to the threat of the lagoon were high levels of plastic waste and metal pollution. Hence, if current trend continues, the possibility of further degradation is very high. The main impact of this research was to provide evidence to the gradual disappearance of the Fosu lagoon.